Avaliação in vitro e in vivo da compatibilidade sanguínea entre muares, equinos e asininos - Firmino, Paulo Ricardo (Universidade Federal Rural do Semi-Árido, 2018)
Mule are hybrid animals resulting from mating between equine species (Equus caballus) and asinine (Equus asinus). Like any equine used in domestic work and sports, mules are subject to accidents, traumas and diseases that cause blood loss. In the literature on transfusion in large animals there is no work that deals with blood compatibility or transfusion in the muar species, being a question of heterologous transfusion for this species. In the present study, blood compatibility between mule and donor recipients of the equine, asinine and mule species was evaluated through cross-reactivity of compatibility and transfusion evaluation. In the first phase, the in vitro compatibility was investigated through cross-reactivity tests, major and minor, in which 12 receiving mule were tested with five specimens of each species. The second phase consisted of evaluation of in vivo compatibility by homologous and heterologous blood transfusion for muar species, where nine mules were divided into 3 groups, and each group received blood from one of the three species. Data from the cross-reactions were analyzed by Kruskal-Wallis and Pearson's Chi-Square tests, and by two-way analysis of variance, followed by the Tukey and Bonferoni tests to evaluate differences between groups and times, at 5% respectively. There was a 76% compatibility rate in the largest reaction for asinines, 51.7% for horses and 71.7% for mules, with mean agglutination scores of 0.42, 1.20 and 0.60, respectively. In the smallest reaction, 18.3% were observed for asinines, 45% for horses and 73.3% for mules, with mean agglutination scores of 2.20, 1.17 and 0.47, respectively. Two animals showed fasciculations compatible with RNHF, but there were no changes in clinical, hemogasometric and biochemical parameters indicating hemolysis in any group. Positive reaction in the major post-transfusional test of the receptor against its donor occurred on average of 4 days for horses, 3.3 for asininos and 5.3 for mules. Transfusion therapy with heterologous equine and asinine blood in a first transfusion proved to be compatible and safe when cross-reacting
Keywords: Transfusão; reação cruzada; aglutinação; xenotransfusão; Transfusion; crossmatching; agglutination; xenotransfusion; CIENCIAS AGRARIAS::MEDICINA VETERINARIA